2013
DOI: 10.1111/jpc.12112
|View full text |Cite
|
Sign up to set email alerts
|

Central venous access device‐related infections in patients with haemophilia

Abstract: CVAD-related infection in this Australian population was comparable to rates described in the medical literature. Ongoing surveillance for infection rates is important to provide an up-to-date assessment of risks associated with CVAD use in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
3
5
0
Order By: Relevance
“…Non‐infectious complications were the most common reason for CVAD removal. Incidence of mechanical complications is similar to previously reported , but the malfunction rate seems to be higher than that previously reported . When comparing to the findings of a meta‐analysis , CVADs remained in situ for twice as long; the median life span was 1159 days (3.2 years) in our cohort compared to 578 days (95% CI 456–733 days) in the meta‐analysis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Non‐infectious complications were the most common reason for CVAD removal. Incidence of mechanical complications is similar to previously reported , but the malfunction rate seems to be higher than that previously reported . When comparing to the findings of a meta‐analysis , CVADs remained in situ for twice as long; the median life span was 1159 days (3.2 years) in our cohort compared to 578 days (95% CI 456–733 days) in the meta‐analysis.…”
Section: Discussionsupporting
confidence: 88%
“…This relatively large nationwide study of 106 CVADs in 58 paediatric patients with 137 971 CVAD followup days reports a very low CVAD-related bloodstream infection rate: 0.12/1000 CVAD days for all and 0.10/ 1000 for non-inhibitor patients. Previous reports have described a wide variety of higher infection rates (0.2-3.4 infections/1000 CVAD days) [1,2,[4][5][6][11][12][13]. In a large meta-analysis with 2704 haemophilia patients and 2973 CVADs [3], infection was the most common reason for removal and the incidence of infection was 0.66/1000 catheter days.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 39% of ports removed due to complications were not replaced and the patient was successfully managed subsequently with peripheral venous access. The infection rate in this large cohort was comparable or somewhat higher than those from previously published data [12][13][14][15][16][17][18][19][20]. This may be because only Four ports with a complication at removal were no longer required.…”
Section: Discussionsupporting
confidence: 71%
“…The infection rate in this large cohort was comparable or somewhat higher than those from previously published data . This may be because only ports that had been removed were included and those that were still in situ without complications were excluded thus giving a selection bias towards increased infections.…”
Section: Discussionsupporting
confidence: 58%
“…A more recent study from Finland of 58 paediatric haemophilia patients with CVADs found a very low bloodstream infection rate (0.12/1000 CVAD days) nationwide . A 1992‐2009 study from Australia reported the overall incidence of confirmed CVAD‐related bloodstream infection was 0.42 per 1000 CVAD days (95% CI: 0.31‐0.58/1000) and that 29 (51.8%) of 56 patients experienced CVAD‐related infections . The 2002‐2009 International Immune Tolerance Induction (I‐ITI) study, which included patients from 21 countries across Europe, North America, Oceana and Asia, reported that 41 of 99 (41%) patients with CVADs experienced an infection, with an overall infection rate of 0.94 per 1000 CVAD days (interquartile range 0‐1.7/1000) .…”
Section: Discussionmentioning
confidence: 99%